Antenatal corticosteroid treatment in singleton, small‐for‐gestational‐age infants born at 24–31 weeks' gestation: a population‐based study. (10th November 2015) - Riskin‐Mashiah, S; Riskin, A; Bader, D; Kugelman, A; Boyko, V; Lerner‐Geva, L; Reichman, B; ,
Abstract : Objective: To assess the impact of antenatal corticosteroid therapy on mortality and severe morbidities in preterm, small‐for‐gestational‐age (SGA) neonates compared with preterm non‐SGA neonates. Design: Population‐based study. Setting/population: Israel National Very Low Birth Weight infant database from 1995–2012. Methods: Singleton infants of 24–31 weeks' gestation, without major malformations. Antenatal corticosteroids were considered either any treatment or no treatment. Main outcome measures: Univariate and multivariable logistic regression analyses were performed to assess the effect of antenatal corticosteroids on neonatal mortality and a composite adverse outcome of mortality or severe neonatal morbidity. Results: Among the 10 887 study infants, 1771 were SGA. Of these, 70.4% of SGA and 66.7% of non‐SGA neonates were exposed to antenatal corticosteroids. Among SGA neonates, antenatal corticosteroids were associated with decreased mortality (32.2 versus 19.3%, P  < 0.0001) and composite adverse outcome (54.1 versus 43.4%, P  < 0.0001), similar to the effect in non‐SGA neonates (mortality 26.7 versus 12.2%, P  < 0.0001; composite outcome 50.5 versus 34.6%, P  < 0.0001). Multivariable logistic regression analyses demonstrated a 50% reduction in mortality risk among SGA and 57% reduction in non‐SGA neonates exposed to corticosteroids [OR = 0.50, 95% confidence interval (95% CI) 0.39–0.64 and OR = 0.43, 95% CI 0.38–0.47, respectively], P ‐value for interaction = 0.08. Composite adverse outcome risk was significantly reduced in SGA (OR = 0.67, 95% CI 0.54–0.83) and non‐SGA infants (OR = 0.57, 95% CI 0.52–0.63), P ‐value for interaction =   0.04. Conclusions: Antenatal corticosteroids significantly reduced mortality and severe morbidities among preterm SGA neonates, with slightly a less pronounced effect compared with non‐SGA preterm infants. Antenatal corticosteroids should be given to fetuses suspected of intrauterine growth retardation, at risk for preterm delivery, in order to improve perinatal outcome. Tweetable abstract: Antenatal steroids reduced mortality and severe morbidities among singleton, preterm SGA neonates. Tweetable abstract: Antenatal steroids reduced mortality and severe morbidities among singleton, preterm SGA neonates.